Negotiating Diversity: Experiential Learning and the Formation of Multicultural Awareness among Muhammadiyah Youth Cadres - Izuddin, Azmi; Ujilast, Farhan Alif; Wikantama, Panji Tegar; Ismail, Syafiq Rahman bin (Universitas Muhammadiyah Surakarta, 2026)
The growing intensity of religious polarization, identity-based tensions, and declining intercultural engagement among youth has raised significant concerns regarding the effectiveness of conventional tolerance education in plural societies. Within the context of Indonesian Muslim youth movements, multicultural awareness is frequently promoted through normative religious discourse, yet often lacks meaningful experiential engagement capable of transforming social perception and civic behavior. This article aims to examine how experiential learning contributes to the formation of multicultural awareness among Muhammadiyah youth cadres through direct encounters with religious diversity. This research employed a qualitative design using a transcendental phenomenological approach. Ten active cadres of the Ikatan Pelajar Muhammadiyah in East Java who participated in the Pelatihan Dai Pelajar Muhammadiyah (PDPM) III 2025 program were purposively selected as participants. Data were collected through in-depth semi-structured interviews, reflective journals, and field observations during interfaith visits to religious communities, including churches, Buddhist temples, and indigenous belief groups. The data were analyzed using phenomenological thematic analysis involving horizontalization, thematic clustering, and interpretive synthesis. The findings reveal that experiential encounters with religious diversity generated significant emotional, cognitive, and behavioral transformations among participants. Direct interaction disrupted inherited stereotypes, encouraged reflective reinterpretation of Islamic identity within plural democratic contexts, and fostered emerging commitments toward inclusive civic engagement. Multicultural awareness developed not through abstract doctrinal instruction alone, but through emotionally meaningful encounters, dialogical reflection, and ethical negotiation of coexistence. The study highlights the strategic role of experiential learning in cultivating socially engaged, democratically oriented, and multicultural Muslim youth within increasingly polarized societies.